Legal Language and Theatrical Presence: Transforming a Legal Inquiry into Theatre in version 1.0’s Deeply Offensive And Utterly Untrue - David A. Williams (Law Text Culture, 2010)
In late 2005, it was revealed that the Australian monopoly wheat exporter AWB Ltd had significantly breached Australian Government backed UN sanctions by paying A$290 million in bribes or ‘kickbacks’ to the Iraq Government.1 As the purpose of these sanctions was to prevent Saddam Hussein’s Government from gaining access to hard currency with which he might purchase or develop weapons, Australian media reportage regularly referred to AWB Ltd’s ‘kickback’ payments as the ‘wheat-for-weapons’ scandal. To investigate the scandal, the Australian Government established the Inquiry into Certain Australian Companies in Relation to the UN Oil-for-Food Programme (the Cole Inquiry). Presided over by Commissioner Terence Cole QC, the high-profile inquiry undertook a forensic investigation of the legally and ethically murky world of international wheat trade.